The Influence of Discipline and Work Environment on the Quality of Public Services through Motivation in Tungkal Ilir District, Tanjung Jabung Barat Regency - Ariyanto, Ariyanto; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti Publisher, 2025)
This study aims to provide an overview of discipline, work environment, motivation, and the quality of public services in Tungkal Ilir District, as well as to examine and analyze the influence of discipline and work environment on public service quality through motivation in Tungkal Ilir District, Tanjung Jabung Barat Regency. This research employs a descriptive-verificative approach and uses Partial Least Squares (PLS) analysis. Based on the results of the descriptive analysis, it explains that the discipline variable (X1) obtained a total score of 5,542 with an average score of 346 and is in the Very High category, the work environment (X2) obtained a total score of 4,181 with an average of 348 and is included in the Very Good category, motivation (Y) obtained a total score of 4,901 with an average of 350 and is included in the Very High category and the quality of public services (Z) obtained a total score of 4,154 with an average of 346 and is in the Very Good category. The results show that discipline and work environment have a positive and significant effect on motivation and public service quality, both directly and indirectly through motivation. Good discipline encourages higher motivation and leads to improved service quality, while a conducive work environment strengthens employee motivation and results in better public services. Motivation plays an important role as a mediating factor in linking discipline and work environment with improvements in public service quality.